Jack Douglas 1994 - "Historical Footnotes of Santa Clara Valley" - Castellano, Alcario:::creator:::::::::::: (2024)
Video and transcripts of a lecture at a university involving the historical footnotes of the Santa Clara Valley, with guest speaker Jack Douglas.